Effect of hypoglycemic events on cognitive function in individuals with type 2 diabetes mellitus: a dose–response meta-analysis - Ye, Min; Yang, Qiqi; Zhang, Lele; Song, Hudie; Fu, Qin; Qian, Jun; Xie, Hongyu; Yuan, Aihong (Frontiers in Neurology, 2024)
Background Type 2 diabetes mellitus (T2DM) is widely acknowledged as a vital warning sign contributing to cognitive dysfunction. However, there is still a lack of consensus on whether hypoglycemic events resulting from poor glycemic control increase the risk of cognitive dysfunction in people with diabetes, and the potential dose–response correlation between hypoglycemic events and cognitive dysfunction remains unexplored. The primary objective of the current study was to assess the contribution of hypoglycemic events to cognitive dysfunction in T2DM patients and the dose–response correlation between the two. Methods A comprehensive search of nine major databases was executed from inception to May 2023. We screened all observational studies examining the connection between hypoglycemia and cognitive dysfunction. The DerSimonian-Laird method was used to compute the combined risk ratio (RR) and its 95% confidence interval (CI). Additionally, dose–response analysis was employed to investigate the correlation between the frequency of hypoglycemia and the likelihood of cognitive dysfunction. Results A total of 30 studies of different levels in 17 articles with 3,961,352 participants were included in this review. The pooled RR for the connection of hypoglycemia and the likelihood of cognitive dysfunction was 1.47 (95% CI: 1.35–1.60). Subgroup analyses showed that the pooled RR for the likelihood of cognitive dysfunction was 1.20 (95% CI: 1.11–1.31) for one episode of hypoglycemia, 1.41 (95% CI: 1.05–1.88) for two episodes of hypoglycemia, and 1.62 (95% CI: 1.20–2.91) for three or more episodes of hypoglycemia. Dose–response analysis showed a linear dose–response relationship between hypoglycemia and the likelihood of cognitive dysfunction (exp (b) = 1.178694, z = 7.12, p < 0.001). Conclusion Our investigations demonstrated a 47% heightened likelihood of cognitive dysfunction in individuals with hypoglycemia compared to those without. Furthermore, the likelihood of cognitive dysfunction climbed by 17.87% for every subsequent episode of hypoglycemia. Therefore, long-term monitoring of blood glucose, periodic screening of cognitive function, and moderate health education should be encouraged, which will be beneficial for people with diabetes to prevent hypoglycemic events and cognitive dysfunction. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, CRD42023432352.